Light-transmitting precast wall - Wan Ali, Wan Muhammad Amar Nasrul (2022)
The construction industry has widely used the precast element in building or any structure. The wall constitutes most of the building elements. The light-transmitting precast wall is a precast wall innovation. The ability to transmit light that light-transmitting precast walls have can give a lot of benefit to the building and environment. The building that installs the light-transmitting precast wall can reduce its consumption of electricity, maximize natural light, and even look more aesthetic. The light-transmitting precast wall is still a precast wall. The light-transmitting precast wall also has the advantages of the current precast wall on the market. The light-transmitting precast wall uses optical fibre as the component to transmit the light. The optical fibre can also be the reinforcement for the precast wall. As a result, the precast wall will obtain more strength than an ordinary precast wall. Optical fibre is a suitable innovation in order to make the green construction industry.